ANALISIS KORELASI KEDISIPLINAN DAN PROFESIONALISME GURU PAI DENGAN PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PAI SDN INPRES MARGAPURA BOLANO LAMBUNU - Mistiani, Wiwin (Paedagogia: Jurnal Pendidikan, 2017)
This study aims to (1) find out the correlation of Islamic Education teacher’s discipline with the achievement of student learning on the subject of Islamic Education at SDN Inpres Margapura (2) to know the correlation between the professionalism of Islamic Education teachers with the achievement of student learning on the subject of Islamic Education at SDN Inpres Margapura, and (3) to know the correlation of discipline and professionalism of Islamic Education teachers with student achievement on Islamic Education at SDN Inpres Margapura. This study uses quantitative approach. The population in this study was all students of class VI SDN Inpres Margapura Academic Year 2016/2017 which amounted to 45. The sample is determined by using proportional random sampling technique using a formula developed by Isaac and Michael. Data were obtained by using questionnaires, observation, interviews and documentation. Data analysis techniques include descriptive analysis, and correlation analysis. The result of research shows that (1) there is a significant correlation between Islamic education teacher’s disciplines with student achievement of SDN Inpres Margapura in Islamic Education Lesson, with significance level of 5% correlation index of both variables of 0.452 means strong enough. (2) There is a significant correlation between professionalism of Islamic education teacher and student achievement of SDN Inpres Margapura on Islamic education subject with significance level of 5% relation index of both variables of 0.661 is strong, (3) There is a correlation between discipline and professionalism teachers of Islamic education with the achievement of students of SDN Inpres Margapura on Islamic education subjects, with a significance level of 5% index of relations between the two variables of 0.663 means strong. Contribution of variables of discipline and professionalism of teachers of Islamic Education simultaneously on learning achievement Students of SDN Inpres Margapura In Islamic Education Lesson is 43.96% and the remaining 56.04% is determined by other variables outside of this research including the level of intelligence/ intelligence, interests, talents, motivation, health, parenting parents and others.